Virtual exchange program building: an assessment-based approach - Nancy L. Ruther; Alexa K. Jeffress; Lu Shi; Sarah Rabke (University of Groningen Press, 2021)
Virtual Exchange (VE) provides a strategic approach for higher education institutions to internationalize. This study investigated how a USA Community College (US-CC) system and their partners started and grew their internationalization program through VE with teacher training, assessment, and support from a nonprofit bridge organization. Data were collected on program growth over three years, 2017-20, totaling 13 modules, 29 faculty, and 14 campuses. Cumulatively, students completed 341 pre-module and 202 post-module surveys which assessed the community colleges' student learning goals: intercultural competence and awareness of the wider world, confidence in finding success in the global workforce, and ability to deploy 21st century skills (e.g. technology and teamwork). Quantitative and qualitative results provided concrete and nuanced evidence of program effectiveness and suggested positive impact. Our findings have two main implications: (1) positive student impact can help grow and sustain VE and other international programming; and (2) teacher training informed by and adapted with student assessment can help institutionalize VE programs.